Enhanced Terrestrial Carbon Export From East Antarctica During the Early Eocene. Issue 2 (3rd February 2022) - Inglis, Gordon N.; Toney, Jaime L.; Zhu, Jiang; Poulsen, Christopher J.; Röhl, Ursula; Jamieson, Stewart S. R.; Pross, Jörg; Cramwinckel, Margot J.; Krishnan, Srinath; Pagani, Mark; Bijl, Peter K.; Bendle, James
Abstract: Terrestrial organic carbon (TerrOC) acts as an important CO2 sink when transported via rivers to the ocean and sequestered in coastal marine sediments. This mechanism might help to modulate atmospheric CO2 levels over short‐ and long‐ timescales (10 3 –10 6 years), but its importance during past warm climates remains unknown. Here we use terrestrial biomarkers preserved in coastal marine sediment samples from Wilkes Land, East Antarctica (∼67°S) to quantify TerrOC burial during the early Eocene (∼54.4–51.5 Ma). Terrestrial biomarker distributions indicate the delivery of plant‐, soil‐, and peat‐derived organic carbon (OC) into the marine realm. Mass accumulation rates of plant‐ (long‐chain n ‐alkane) and soil‐derived (hopane) biomarkers dramatically increase between the earliest Eocene (∼54 Ma) and the early Eocene Climatic Optimum (EECO; ∼53 Ma). This coincides with increased OC mass accumulation rates and indicates enhanced TerrOC burial during the EECO. Leaf wax δ 2 H values indicate that the EECO was characterized by wetter conditions relative to the earliest Eocene, suggesting that hydroclimate exerts a first‐order control on TerrOC export. Our results indicate that TerrOC burial in coastal marine sediments could have acted as an important negative feedback mechanism during the early Eocene, but also during other warm climate intervals. Plain Language Summary: Organic matter from the terrestrial biosphere can be transferred into rivers and eventually deposited in the ocean. This process helps to remove carbon dioxide from the atmosphere over long (>1, 000 years) timescales. However, the importance of this process in warm climates is one of the most poorly understood aspects of the climate system. One way to test the behavior of the Earth in warmer‐than‐present climate states is to examine the geological record. Here we analyzed marine sediments deposited close to the Antarctic shoreline to quantify organic carbon burial during an ancient warm interval (the early Eocene, 56 to 48 million years ago). We analyzed biomolecules from plants and microbes to determine how much organic matter was derived from the terrestrial biosphere. We found evidence for increased terrestrial organic carbon burial in marine sediments during the early Eocene. This process could help to remove carbon dioxide from the atmosphere and is relevant to other episodes of climate change during Earth's history. Key Points: Terrestrial organic carbon is an important CO2 sink when transported via rivers to the ocean and sequestered in coastal marine sediments Biomarkers indicate enhanced terrestrial organic carbon burial during early Eocene—this could have acted as a negative feedback mechanism Hydrology regulates organic carbon export from the terrestrial biosphere at this site